Factors affecting nutritional anemia in elderly Filipinos living in six municipalities of Cavite - Cheong, Revelita Lacayon
A study on the factors affecting nutritional anemia in 301 apparently healthy elderly Filipinos in six municipalities of Cavite was conducted from June to December, 1992. The study aimed to determine the iron and folacin status among the anemic and non-anemic subjects using serum iron, serum total iron binding capacity (TIBIC), transferrin saturation index (TSI), free erythrocyte protoporphyrin (FEP), mean corpuscular hemoglobin concentration (MCHC) and red cell folate as indicators. Red cell morphologic classification for anemia and Arneth's test to identify hypersegmentation of neutrophils for folate deficiency were also included. Likewise, adequacy of nutrient intakes and the effects of phytin and some socioeconomic factors such as age, sex, civil status, family size, level of education and income to hemoglobin were also studied.